MOCK CONFERENCE IN PRE-SERVICE TRANSLATORS TRAINING - Mirzoyeva, Leila; Gatiat, Aissulu (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
The given research deals with one of the most important issues related to pre-service translators’ training such as both language and professional skills development in Kazakhstani settings. Thus, skills in oral translation from English into Kazakh and/or Russian and vice versa are in pretty high demand these days that is why one of the aims of Translation and interpreting internship course is to develop the consecutive translation skills of pre-service translators. So, to imitate the conditions of interpreters’ work we conducted the mock conference dedicated to the main problems of Translation studies and Linguistics in the frame of the above mentioned course. The main idea of this case study was to involve our students into both research and professional activity as well as to develop their language and consecutive translation skills. Our research population included 47 students who worked both as presenters and interpreters in the frame of the mock conference procedure. Then we conducted the opinion survey using the online tools provided by the Moodle platform (in our case, the option of Critical incident survey had been chosen as the most appropriate one).